ANALYSIS OF CONSUMER BEHAVIOR TOWARDS DECISION TO PURCHASE Tahu AT UD MAKMUR ETERNAL - edi (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
PT Indo Tirta Abadi Plant Gempol is one of the plastic packaging manufacturing companies, which has implemented the FSMS (Food Safety Management System) based on the international FSSC 22000 standard since October 2016. With demands for food safety requirements that continue to grow accompanied by customer demands regarding the quality of PT Indo products Tirta Abadi Plant Gempol must be able to maintain the quality management system that has been achieved by the company and achieve a competitive advantage in the plastic packaging industry, by ensuring that the products produced are quality products and are safe for consumption through the effective implementation of FSSC 22000. The objectives of this study were (1) to determine the effectiveness of the application of ISO FSSC 22000 at PT. Indo Tirta Abadi with internal and external audit indicators. (2) knowing the minimum criteria for auditors in implementing ISO FSSC 22000. (3) knowing the alternative strategy choices in implementing ISO FSSC 22000, there are three priority alternative strategies selected based on the calculation results using the AHP method, namely (1) labor efficiency which has been stated in food quality and safety policy with a weight value of 0.206,(2) increasing the volume / time interval of testing with reference to standard specifications that have been determined in general procedures as a guarantee for the quality of products that are safe for consumption with a weight value of 0.162, (3) team injection to build togetherness in implementing procedures, work instructions and applicable regulations related to food safety with a weight value of 0.137.